Using Infographics to Strengthen Academic Integrity: An Experience of the School of Educational Sciences of the Distance State University of Costa Rica - Solano Fallas, Andrés (2023)
This article is a systematization of the experience carried out by the Academic Integrity Team (ETIA in Spanish) of the School of Educational Sciences (ECE in Spanish) of the State Distance University of Costa Rica (UNED in Spanish), with the aim of raising awareness of academic integrity as a response to the increase in fraudulent practices that occurred during the year 2020, as a result of the massive virtualization of subjects, on account of the COVID-19 pandemic. Seeking to transcend the traditional punitive approach to academic fraud used as a strategy, two series of ten infographics were produced, under three key axes (awareness training, theoretical, and reflective), which address both regulatory theoretical aspects of academic fraud and plagiarism, as well as surrounding elements of learning that affect academic success. Having said this, the main result of the experience was that the work carried out by the ETIA was reflected in a reduction in the number of complaints about academic fraud and the like filed with the ECE, which suggests not only the relevance of the strategy, but also of the theoretical axes that guided it.